Pengaruh Inflasi Dan Debt To Equity Ratio (Der) Terhadap Nilai Perusahaan Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (Bei) Periode 2022-2024 - St. Nur Arsyh Ismayanti. S; Manuel August Todingbua; Benyamin Mongan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study aims to analyze the effect of inflation and Debt to Equity Ratio (DER) on firm value, proxied by Price to Book Value (PBV), in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The data used are secondary data obtained from annual financial statements, publications of the Central Bureau of Statistics (BPS), and Bank Indonesia (BI). The analytical method employed is panel data regression using the Fixed Effect Model (FEM), selected based on the results of the Chow and Ha usman tests. The results show that partially, inflation has no significant effect on firm value, indicating that the food and beverage sector tends to be resilient to inflation due to the essential nature of its products. Meanwhile, the Debt to Equity Ratio (DER) has a positive and significant effect on firm value, implying that the optimal use of debt within the capital structure can increase the company’s market value. Simultaneously, inflation and DER significantly affect PBV, confirming that macroeconomic and capital structure factors play an important role in determining firm value. The findings of this study are expected to serve as a reference for company management in determining optimal financing policies and for investors in assessing investment potential in the food and beverage sector.